A Comparative Study Between Indonesia and Malaysia on the Role of Notaries and Advocates - Abdillah, Satrio; Ghapa, Norhasliza; Makhtar, Maheran (Universitas Semarang, 2023)
This research aims to compare the roles of notaries and advocates in Indonesia and Malaysia. The urgency of this research is to provide better insight into the topic. The novelty of this research lies in the comparative approach offered in this analysis in the legal context of Indonesia and Malaysia. This research uses a qualitative approach with data sources in documentation and observation. The analysis tool chosen is Nvivo 12 Plus. The findings of this study succeeded in identifying striking similarities and differences in the roles of these two professions. The main similarity in the role of notaries in Indonesia and Malaysia is the function of legalizing and enforcing the validity of legal documents. Notaries in both countries certify documents and ensure compliance with applicable laws. However, the most significant difference lies in the two countries' scope of duties, legal authority, and notary education systems. The main similarities in the role of advocates in Indonesia and Malaysia include legal representation, providing legal advice, and filing legal documents. However, the main differences relate to the scope of the case, legal system, educational requirements, legal language, and legal culture. This shows differences in the two countries' legal contexts and legal demands. Thus, the roles of notaries and advocates in Indonesia and Malaysia have basic similarities in legalizing documents and legal representation but significant differences in the scope of duties, legal authority, education system, and legal and cultural context.